Factors associated with nicotine replacement therapy use among hospitalised smokers. (7th February 2018) - Chui, Chang Yue; Thomas, Dennis; Taylor, Simone; Bonevski, Billie; Abramson, Michael J.; Paul, Eldho; Poole, Susan G.; Weeks, Gregory R.; Dooley, Michael J.; George, Johnson
Abstract: Introduction and Aims: Nicotine replacement therapy (NRT) is recommended as a smoking cessation aid for hospitalised smokers. We examined factors associated with NRT use during hospitalisation and after discharge, and NRT uptake when systematically offered free of cost. Design and Methods: A nested analysis was conducted using data from a clinical trial that evaluated the effectiveness of a pharmacist‐led smoking cessation intervention in 600 hospitalised smokers. Results: NRT was used at least once by 285 (48%) participants during hospitalisation and by 287 (48%) participants during the 12 months post‐discharge. Heavy smokers and those who expressed interest in using NRT for their next quit attempt at baseline interview were more likely to use NRT during hospitalisation [odds ratio (OR) 1.94, 95% confidence interval (CI) 1.38, 2.74; OR 2.09, 95% CI 1.48, 2.95] and after discharge (OR 1.70, 95% CI 1.20, 2.41; OR 1.97, 95% CI 1.39, 2.79). Those using six or more medications were more likely to use NRT during hospitalisation (OR 1.65, 95% CI 1.05, 2.61). Post‐discharge NRT users were more likely to have been initially admitted for a respiratory or cardiac problem (OR 1.51, 95% CI 1.05, 2.18). When NRT was offered free of cost to a subset of patients ( n = 300), 157 (52%) used NRT during hospitalisation. Nicotine dependence and interest in using NRT predicted its use (OR 2.26, 95% CI 1.38, 3.70; OR 2.58, 95% CI 1.58, 4.20). Discussion and Conclusions: Targeting heavy smokers, those with cardio‐respiratory conditions and those interested in using NRT regardless of regimen complexity could improve NRT uptake.